A study to analyze the correlation between nutritional dermatoses with socioeconomic status, dietary fallacies and growth in children 1 to 5 years of age, in and around rural area - Kumar D., Pavan (International Journal of Contemporary Pediatrics, 2018)
Background: Little information is available about the prevalence of skin conditions among the children in general population. Skin conditions vary in frequencies and severity in different age groups, different geographical locations and under different definitions of skin diseases. Low socioeconomic status, malnutrition, overcrowding, poor standards of hygiene are important factors accounting for development of nutritional dermatoses in developing countries such as India. The objective of the present research was to study the association between nutritional dermatoses with Socioeconomic status, dietary fallacies and growth in children 1 to 5 years of age. Methods: A cross sectional study was conducted in a rural based medical college of Dakshina Kannada District in Karnataka among the one to five years age children, who were attending the Pediatric out patient with nutritional skin lesions from the month of November 2012 to October 2013. The sample size was estimated as 150 children. Results: In present study, 76.00% (114) of children fall in the group of under nutrition and 73.33% (110) children is having the causative factor as Dietary Fallacies. Majority of children 60.66% (91) with nutritional dermatoses belongs to class IV socio-economic status according to B.G Prasad classification, 27.33% (41) belongs to class III and 12.00% (18) children belongs to class V. 64.66% (97) of children with nutritional dermatoses were underweight, 47.33% (71) of children showed wasting and 35.30% (53) children were stunted. Conclusions: Lower socioeconomic condition and dietary fallacies were the two most causative factors which had an adverse effect on nutritional status of child causing dermatoses. Nutrition deficiency had an impact of early transitional growth failure and delay in the achieving mile stone.